The prevalence of cardiac sarcoidosis is underestimated: [18F]FDG-PET is the answer. (20th July 2021) - Borges-Rosa, J; Oliveira-Santos, M; Silva, R; Lopes De Almeida, J; Goncalves, L; Costa, G; Ferreira, MJ
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Overt cardiac involvement is reported in 5% of patients with sarcoidosis, although autopsy and imaging studies suggest higher prevalence, worldwide variation. The role of 18F-fluorodeoxyglucose positron emission tomography ([18F]FDG-PET) in non-invasive diagnosis and follow-up has increased in the last decade. Purpose: Our goal is to describe the prevalence, clinical manifestations and outcomes of cardiac sarcoidosis (CS), diagnosed through [18F]FDG-PET, in a southern European population. Methods: We included all patients with histological diagnosis of extracardiac sarcoidosis screened with [18F]FDG-PET between 2009 and 2020. We collected data on clinical manifestations, cardiac magnetic resonance (CMR) results, and mortality outcomes and compared those with and without cardiac involvement. We applied the criteria for the diagnosis of CS from Heart Rhythm Society. Results: Of the 400 patients screened with [18F]FDG-PET, 128 had a histological diagnosis of extracardiac sarcoidosis (54.7% females, mean age 51.0 ± 14.2 years). None underwent endomyocardial biopsy. Ten patients had a pattern of [18F]FDG uptake consistent with CS defined as diffuse (n = 5), focal (n = 3), and focal on diffuse (n = 2). Of the 128 patients, 14 also underwent CMR, which identified 2 subjects with positive findings in both modalities and 3 additional patients: focal (n = 1), multifocal mid-wall (n = 2), focal mid-wall (n = 2), and multifocal subepicardial (n = 1) delayed gadolinium enhancement. Overall, 13 patients (10.2%) fulfilled the criteria for probable CS (53.8% female, mean age 56.2 ± 12.6 years), all with multiorgan involvement, mostly lung and lymph nodes (each 92%), followed by skin and central nervous system (each 15%). Median left ventricle ejection fraction was 62% [55-65] and there were cardiac manifestations of CS in 6 patients (46%): sick sinus syndrome (n = 2), complete heart block (n = 1), frequent premature ventricular complexes (n = 1), ventricular tachycardia plus heart failure (n = 1), and bifascicular block plus heart failure (n = 1). Eleven patients (85%) with probable CS were medicated with immunosuppressant drugs: corticosteroids (n = 9), methotrexate (n = 4), and azathioprine (n = 2). Four patients with previous [18F]FDG screening were revaluated after treatment, each showing no cardiac uptake.  After a mean follow-up of 4.0 ± 1.0 years, mortality was three-fold higher in patients with cardiac involvement, despite the absence of statistical significance (15% vs. 5%, P = 0.151). Conclusions: In a southern European population with histological extracardiac sarcoidosis, the prevalence of cardiac involvement was 10.2%, most asymptomatic. [18F]FDG-PET improves the diagnostic yield and plays an important role in monitoring response to therapy. The higher mortality trend in those with CS needs to be ascertained in longer follow-up.